2019
DOI: 10.3390/molecules24112178
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Dimeric Abietanoid Peroxides from the Bark of Cryptomeria japonica

Abstract: Three new dimeric abietane-type diterpenoids, abieta-6,8,11,13-tetraen-12-yl 12-hydroxyabieta-8,11,13-trien-7α-yl peroxide (1), abieta-6,8,11,13-tetraen-12-yl 12-hydroxyabieta-8,11,13-trien-7β-yl peroxide (2), and 12-hydroxyabieta-8,11,13-trien-7β-yl 7-oxoabieta-5,8,11,13-tetraen-12-yl peroxide (3), together with four known abietane-type diterpenoids (4–7) were isolated from the methanol extract of the bark of Cryptomeria japonica. Their structures were elucidated on the basis of spectroscopic analysis and com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…The diterpenoid constituents of Cryptomeria japonica and Taxodium distichum have been studied more extensively [24,25,26,27,28,29,31,32,33,34,35,38,39,40,41,42,48] and references therein]. However, none of these earlier studies reported the natural product compositions of the total resin/plant extracts, but instead the mixtures were separated by liquid or high-pressure liquid chromatography (LC or HPLC), followed by structure determination of each compound by NMR, HRMS for elemental composition, and sometimes MS (underivatized by direct insertion probe).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The diterpenoid constituents of Cryptomeria japonica and Taxodium distichum have been studied more extensively [24,25,26,27,28,29,31,32,33,34,35,38,39,40,41,42,48] and references therein]. However, none of these earlier studies reported the natural product compositions of the total resin/plant extracts, but instead the mixtures were separated by liquid or high-pressure liquid chromatography (LC or HPLC), followed by structure determination of each compound by NMR, HRMS for elemental composition, and sometimes MS (underivatized by direct insertion probe).…”
Section: Resultsmentioning
confidence: 99%
“…The identification of cymenylferruginol ( a26 ), a triterpenoid like the chamaecydins, in both the extant and fossil resins is of interest because natural product chemists are identifying numerous dimer terpenoids, i.e., mono-to-diterpenoid, sesqui-to-diterpenoid and diterpenoid dimers, in extant plants [25,26,36,41,48]. Therefore, the formation mechanism is for example ferruginol reacting at C-7 with cymene to produce 7-cymenylferruginol, 6-deoxotaxodione reacting at C-7 and C-14 with sabinene or thujene to form chamaecydin, cadinols reacting with ferruginol at C-7 to yield the various sesquaterpenoids, or peroxidation of ferruginol to dimers [26,41,48,72,73]. Some of these natural products, if adequately concentrated in the extant biomass, may become preserved as tracers in the geological record, as for example cymenylferruginol reported here.…”
Section: Resultsmentioning
confidence: 99%
“…Five abietane-type diterpenoid homodimers with a peroxide linkage, 246–250 , were isolated from Cryptomeria japonica . 147,148 From the same plant, japonicinol A ( 251 ) is a heterodimeric analog of 246–250 bearing a peroxide linkage. 104 The first example of a biscembranoid connected by a peroxide group, bischerbolide peroxide ( 252 ), was isolated from the Formosan soft coral Sarcophyton cherbonnieri .…”
Section: Biosynthesis Of Bisditerpenoidsmentioning
confidence: 99%